2012
DOI: 10.1007/s13277-012-0375-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microsomal metabolism of the food toxicant, benzo(a)pyrene, in Apc Min mouse model of colon cancer

Abstract: The present study was conducted to investigate whether colon tumors were capable of metabolizing benzo (a)pyrene (BaP), and fluoranthene (FLA), two toxicants that belong to the polycyclic aromatic hydrocarbon family of compounds. Microsomes were isolated from the colon tumors of ApcMin mice that received subchronic doses of 50 μg/kg BaP and incubated with either BaP or FLA (3 μM each) alone or in combination and appropriate control groups that received nothing. Subsequent to incubation, samples were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 44 publications
(46 reference statements)
3
15
0
Order By: Relevance
“…Bio-tranformation of FLA by tumor cells may lead to production of intracellular metabolites (Buesen et al, 2002; Myers et al, 2011) whose production rate may have enhanced due to the action of BaP. Co-exposure to both BaP and FLA has been shown to enhance the metabolism of FLA in adipose (Huderson et al, 2010) and colon tumor (Diggs et al, 2012) tissues of a colon cancer mouse model. This situation may aid in the progression of disease as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bio-tranformation of FLA by tumor cells may lead to production of intracellular metabolites (Buesen et al, 2002; Myers et al, 2011) whose production rate may have enhanced due to the action of BaP. Co-exposure to both BaP and FLA has been shown to enhance the metabolism of FLA in adipose (Huderson et al, 2010) and colon tumor (Diggs et al, 2012) tissues of a colon cancer mouse model. This situation may aid in the progression of disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…Disposition of some PAH metabolites in intestinal crypts (Herbst et al, 2006) and the ability of tumor cells to metabolize BaP (Diggs et al, 2012) lend credence to the assumption that localized metabolism of PAHs contribute to cytotoxicity and aid in the neoplastic transformation of polyps.…”
Section: Introductionmentioning
confidence: 98%
“…Long-term exposure to low levels of some PAHs (e.g., pyrene and BaP) has been identified as the cause of cancer in laboratory animals (Diggs et al, 2012). Animal studies have also shown adverse reproductive and developmental effects from PAH exposure while such effects have not commonly been detected in humans (Wells et al, 2010).…”
Section: Chronic or Long-term Health Effectsmentioning
confidence: 99%
“…The greater concentrations of B(a)P metabolites may have elevated plasma ROS levels and increased protein expression of TNF-a, Cyp A, and MMP-9 leading to the pathobiology of abdominal aneurysms observed in our earlier study. Among the different subcellular fractions, the microsomal and mitochondrial fractions registered greater concentrations of B(a)P metabolites as these organelles are rich in CYP family of biotransformation enzymes [39].…”
Section: Resultsmentioning
confidence: 99%